Differential Gene Expression in Rhododendron fortunei Roots Colonized by an Ericoid Mycorrhizal Fungus and Increased Nitrogen Absorption and Plant Growth - Wei, Xiangying; Chen, Jianjun; Zhang, Chunying; Pan, Dongming (Frontiers in Plant Science, 2016)
Ericoid mycorrhizal (ERM) fungi are specifically symbiotic with plants in the family Ericaceae. Little is known thus far about their symbiotic establishment and subsequent nitrogen (N) uptake at the molecular level. The present study devised a system for establishing a symbiotic relationship between Rhododendron fortunei Lindl. and an ERM fungus (Oidiodendron maius var. maius strain Om19), quantified seedling growth and N uptake, and compared transcriptome profiling between colonized and uncolonized roots using RNA-Seq. The Om19 colonization induced 16,892 genes that were differentially expressed in plant roots, of which 14,364 were upregulated and 2,528 were downregulated. These genes included those homologous to ATP-binding cassette transporters, calcium/calmodulin-dependent kinases, and symbiosis receptor-like kinases. N metabolism was particularly active in Om19-colonized roots, and 51 genes were upregulated, such as nitrate transporters, nitrate reductase, nitrite reductase, ammonium transporters, glutamine synthetase, and glutamate synthase. Transcriptome analysis also identified a series of genes involving endocytosis, Fc-gamma R-mediated phagocytosis, glycerophospholipid metabolism, and GnRH signal pathway that have not been reported previously. Their roles in the symbiosis require further investigation. The Om19 colonization significantly increased N uptake and seedling growth. Total N content and dry weight of colonized seedlings were 36.6% and 46.6% greater than control seedlings. This is the first transcriptome analysis of a species from the family Ericaceae colonized by an ERM fungus. The findings from this study will shed light on the mechanisms underlying symbiotic relationships of ericaceous species with ERM fungi and the symbiosis-resultant N uptake and plant growth.